GE_GERICHTE C/28481/2019 vom 13. Dezember 2022 - GE Cour de justice (2022)
PRÊT DE CONSOMMATION;INTERPRÉTATION(SENS GÉNÉRAL);NOVA;FARDEAU DE LA PREUVE | CO.312; CO.18; CC.8; CPC.222.al2; CPC.221.al1.letd; CPC.221.al1.lete; CPC.55